HERPES ZOSTER PADA PASIEN ARTRITIS REUMATOID YANG MENDAPAT TERAPI METOTREKSAT: SEBUAH LAPORAN KASUS - Nanda Earlia; Vella Vella; Arie Hidayati; Aqil Yuniawan Tasrif; Mikyal Bulqiah; Aldilla Prasditha; Karamina Maghfirah (Media Dermato-Venereologica Indonesiana, 2023)
Background: Herpes zoster (HZ) is an acute infection caused by varicella zoster (VZV) reactivation that manifests clinically as groupings of vesicles and eruptions on a reddish skin base, along with unilateral radicular pain that is often localized to one dermatome. Case Ilustration: A 50-year-old woman arrived complaining of uncomfortable wet bumps on her left back. The patient has received consistent care at the Internal Medicine Polyclinic for the past 7 years despite having a prior history of rheumatoid arthritis. In the left posterior thoracic area, there was evidence of a dermatological condition. Groups of vesicles filled with clear fluid were observed there, along with skin that was unilaterally distributed and erythematous, zoosteriform, and plaque-based. Diagnosed with herpes zoster in the patient. Acyclovir, gabapentin, and paracetamol were administered orally. Mupirocin 2% cream and a wet compress with NaCl solution were used as topical treatments. Rheumatoid arthritis (methotrexate and sulfasalazine) treatment was stopped during HZ treatment. Skin blemishes had improved after receiving treatment for two weeks. Conclusion: After a prior varicella assault, the latent endogenous varicella zoster virus (VZV) in ganglionic neurons reactivates to cause herpes zoster. Herpes zoster risk will grow in immune-compromised states.